2015
DOI: 10.1016/j.athoracsur.2015.03.016
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of a Frailty Education Module on Surgical Resident Estimates of Lobectomy Risk

Abstract: Background Frailty is a risk factor for adverse events after surgery. Residents’ ability to recognize frailty is underdeveloped. We assessed the influence of a frailty education module on surgical residents’ estimates of lobectomy risk. Methods Traditional track cardiothoracic surgery residents were randomized to take an on-line short course on frailty (experimental group) or to receive no training (control group). Residents read a clinical vignette, made an initial risk estimate of major complications for l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 19 publications
0
7
0
Order By: Relevance
“…1 ). Table 1 shows the descriptive characteristics of the articles that measured frailty (33%, n = 204) [ 18 – 221 ], whereas Additional file 1 : Table S3 shows the descriptive characteristics of the articles that did not include a frailty measurement.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 ). Table 1 shows the descriptive characteristics of the articles that measured frailty (33%, n = 204) [ 18 – 221 ], whereas Additional file 1 : Table S3 shows the descriptive characteristics of the articles that did not include a frailty measurement.…”
Section: Resultsmentioning
confidence: 99%
“…The Frailty Index was the most popular measure used in emergency departments ( n = 7/33; 21%) [ 93 , 106 , 125 , 131 , 163 , 165 , 195 ] and orthopedics ( n = 4/18; 22%) [ 126 , 189 , 219 , 220 ] (Table 3 ), in Italy ( n = 5/19; 26%) [ 93 , 104 , 106 , 133 ] and Denmark ( n = 3/8; 38%) [ 189 , 219 , 220 ], and in experimental articles ( n = 6/32; 19%) [ 50 , 62 , 166 , 189 , 219 , 220 ]. The Frailty Phenotype was the most popular measure used in cardiology ( n = 6/24; 25%) [ 45 , 89 , 90 , 112 , 172 , 208 ] and surgery ( n = 2/10; 20%) [ 184 , 221 ] (Table 3 ), and in Spain ( n = 4/10; 40%) [ 90 , 112 , 172 , 174 ] and Sweden ( n = 2/6, 33%) [ 92 , 119 ]. Among the 122 articles that reported the prevalence of frailty, the median prevalence was 49%.…”
Section: Resultsmentioning
confidence: 99%
“…104 A US educational interventional study involving cardiothoracic surgery residents showed that online short courses on frailty significantly improved residents' knowledge of frailty and influenced surgical risk estimates. 105 Finally, frailty research may have evolved without taking into account the patient perspective. Frailty can be considered as a highly negative term and being labeled as frail may affect negatively the most vulnerable individuals in various ways.…”
mentioning
confidence: 99%
“…Data from this study were taken from Institutional Review Board-approved prior studies at our institution (The University of Chicago, Chicago, Illinois) [10,11], and this protocol was approved by our Institutional Review Board (IRB17-0448). In these studies, thoracic surgeons and cardiothoracic surgeons in training were recruited to participate from a list provided by the Thoracic Surgery Directors Association, as previously described [10,11]. Anonymized clinical vignettes were developed from patients 60 to 69 years of age who previously underwent lobectomy for lung cancer.…”
Section: Methodsmentioning
confidence: 99%